Self-flame retardant thermoplastic polyaryl ketone resin and synthesis method thereof
By improving the content of nitrogen elements during the synthesis process of polyfordone resin, the problem of combustible flame retardant and thermal stability in existing technologies has been solved, and the thermoplastics aggregation of high flame retardant and heat resistance stability is achieved. Ferramone resin is suitable for the application of high temperature environment.
Patent Information
- Application Number
- CN202411662327.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-20
AI Technical Summary
In the prior art, nitrogen elements account for a small proportion in polymers, resulting in less improvement in flame retardancy and heat resistance of polymers, limiting the application of polymers in high temperature environments.
By using 1,3-dihydrial phenazole-2-ketone, 2,6-dietthylezozoette, and 4,4'-dietthylene ketone during the synthesis process of polyquine resin, and Increase the content of nitrogen elements and synthesize the thermoplastic polytosterone resin with high flame -retardant and high heat resistance through specific reaction steps and conditions.
The high flame retardability and thermal stability of the polymer are realized. The UL-94 flammable testing is V0 level, the glass-based transition temperature is ≥253 ° C, and the inherent viscosity IV is 0.4-0.9. It is suitable for long-term application to high temperature environment.
Smart Images

Figure CN119143990B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyaryl ketone synthesis, and in particular to a novel self-flame retardant thermoplastic polyaryl ketone resin and a synthesis method thereof. Background Art
[0002] With the development of material science and the requirements of high technology, special engineering plastics with high performance and high added value have gradually received attention and favor from the country and enterprises. Polyarylether and polyaryletherketone polymers have the characteristics of high mechanical strength and excellent electrical properties, and have been well utilized in many fields. However, special engineering plastics containing elements such as nitrogen and phosphorus with higher flame retardancy and higher heat stability need to be further developed.
[0003] In the ternary polymers and tetrapolymers in the prior art, the proportion of nitrogen in the polymer is relatively small, resulting in a small improvement in the flame retardancy of the polymer. It is impossible to obtain a polymer with high flame retardancy and high heat stability, which limits the application of the polymer in high temperature environments.
[0004] In view of the above problems in the prior art, the present invention combines many years of design and use experience in related fields to design a new self-flame retardant thermoplastic polyaryl ketone resin and a synthesis method thereof to overcome the above defects. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a novel self-flame retardant thermoplastic polyaryl ketone resin and a synthesis method thereof, which has a high nitrogen content, a high flame retardancy, a high glass transition temperature of 253°C or above, an inherent viscosity of 0.4-0.9, is easy to process, can be used in high temperature environments for a long time, and has a long service life.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for synthesizing a novel self-flame retardant thermoplastic polyaryl ketone resin comprises the following steps:
[0007] (1) Under an inert atmosphere, 1,3-dihydrobenzimidazol-2-one, 4,4'-difluorobenzophenone, 2,6-difluorobenzonitrile, a catalyst and an organic solvent are added to a reaction vessel and stirred, and the temperature is raised to 140-200° C. for reaction for 1-2 hours, 1,3-dihydrobenzimidazol-2-one reacts with the catalyst to generate salt and water, and the reaction system is dehydrated so that the water content of the reaction system is less than or equal to 1000 ppm;
[0008] (2) Prepolymerization reaction: reacting at 160-260° C. for 2-6 hours, wherein the salt in step (1) reacts with 4,4'-difluorobenzophenone and 2,6-difluorobenzonitrile to obtain a prepolymer product;
[0009] (3) Polymerization reaction: Continue to raise the temperature to 180-320°C and react for 2-8 hours to obtain a polymer product;
[0010] (4) dispersing, washing and drying the polymer product of step (3) to obtain a final product;
[0011] The molar ratio of 1,3-dihydrobenzimidazol-2-one, 2,6-difluorobenzonitrile and 4,4'-difluorobenzophenone is 4:1-3:1-3;
[0012] The molar ratio of the 1,3-dihydrobenzimidazol-2-one, the catalyst and the organic solvent is 1:1.08-1.12:5-15.
[0013] Preferably, in step (1), the molar ratio of 1,3-dihydrobenzimidazol-2-one, 2,6-difluorobenzonitrile and 4,4'-difluorobenzophenone is 4:3:1.
[0014] Preferably, in step (1), the reaction temperature of 1,3-dihydrobenzimidazol-2-one and the catalyst is 160-180°C.
[0015] Preferably, in step (1), the catalyst is selected from anhydrous sodium carbonate or anhydrous potassium carbonate, and the organic solvent is selected from any one of diphenyl sulfone, diisopropylbenzene peroxide, N,N-dimethylformamide, cyclopentane, and N-cyclohexylpyrrolidone, or a combination of several thereof.
[0016] Preferably, the prepolymerization reaction in step (2) is carried out at 220° C. for 3 h to obtain a prepolymerization product.
[0017] Preferably, step (3) comprises a first-stage temperature rising reaction and a second-stage temperature rising reaction, and both the first-stage temperature rising reaction and the second-stage temperature rising reaction adopt gradient temperature rising, and the heating rate is 1-5°C / min.
[0018] Preferably, the reaction temperature of the first stage of temperature-raising reaction is 180-280° C., and the reaction time of the first stage of temperature-raising reaction is 2-3 h.
[0019] Preferably, the reaction temperature of the second-stage temperature-raising reaction is 190-320° C., and the reaction time of the second-stage temperature-raising reaction is 2-6 hours.
[0020] Preferably, the washing process of step (4) is: washing the solid powder with an acidic aqueous solution and pure water for multiple times at 60-100° C. until the metal ion content drops below 100 ppm;
[0021] The acidic aqueous solution is a phosphoric acid aqueous solution with a mass fraction of 3%-50%.
[0022] The present invention also provides a novel self-flame retardant thermoplastic polyaryl ketone resin obtained by the above synthesis method, wherein the thermoplastic polyaryl ketone resin has the following general structural formula:
[0023] ;
[0024] Wherein, m and n are the numbers of two repeating units, and both m and n are positive integers, 5≤m≤500, 5≤n≤500.
[0025] The invention is beneficial in that:
[0026] 1. The present invention uses 1,3-dihydrobenzimidazol-2-one as a main monomer, reacts with 2,6-difluorobenzonitrile and 4,4'-difluorobenzophenone respectively, introduces nitrogen into the polymer, increases the proportion of nitrogen in the polymer, and synthesizes a thermoplastic polyaryl ketone resin with high flame retardancy and high glass transition temperature. The UL-94 flammability test reaches V0 level, the glass transition temperature is ≥253°C, the inherent viscosity IV is 0.4-0.9, and when the molar ratio of 2,6-difluorobenzonitrile to 4,4'-difluorobenzophenone is ≥1, the polymer glass transition temperature is ≥289°C. The thermoplastic polyaryl ketone resin has good processability and long service life at high temperature, and can be widely used in high temperature fields as a special material.
[0027] 2. The present invention uses a one-pot process to carry out the reaction, which is simple to operate and does not require the preparation of intermediate products, thus greatly reducing the complexity of the process. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a DSC curve diagram of the thermoplastic polyaryl ketone resin prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] In order to facilitate understanding by those skilled in the art, the present invention is further described below in conjunction with specific embodiments.
[0030] A method for synthesizing a novel self-flame retardant thermoplastic polyaryl ketone resin comprises the following steps:
[0031] (1) Under an inert atmosphere, 1,3-dihydrobenzimidazol-2-one, 4,4'-difluorobenzophenone, 2,6-difluorobenzonitrile, a catalyst and an organic solvent are added to a reaction vessel and stirred, the temperature of the reaction system is raised to 140-200° C., preferably 160-180° C., 1,3-dihydrobenzimidazol-2-one reacts with the catalyst for 1-2 hours to generate salt and water, the reaction system is a white slurry, and the reaction system is dehydrated to make the water content of the reaction system less than or equal to 1000 ppm;
[0032] The molar ratio of 1,3-dihydrobenzimidazol-2-one, 2,6-difluorobenzonitrile and 4,4'-difluorobenzophenone is 4:1-3:1-3;
[0033] The molar ratio of 1,3-dihydrobenzimidazol-2-one, catalyst and organic solvent is 1:1.08-1.12:5-15;
[0034] (2) Prepolymerization reaction: at 160-260° C., the salt in step (1) is subjected to a prepolymerization reaction with 4,4'-difluorobenzophenone and 2,6-difluorobenzonitrile respectively for a reaction time of 2-6 hours to obtain a prepolymer product;
[0035] (3) Polymerization reaction: heating to 180-320°C and reacting for 2-8h to obtain a polymer product. Specifically, the polymerization reaction includes a first-stage temperature rise reaction and a second-stage temperature rise reaction. Both the first-stage temperature rise reaction and the second-stage temperature rise reaction adopt a gradient temperature rise, and the temperature rise rate is 1-5°C / min;
[0036] The reaction temperature of the first stage heating reaction is 180-280°C, the reaction time of the first stage heating reaction is 2-3h, the reaction temperature of the second stage heating reaction is 190-320°C, the reaction time of the second stage heating reaction is 2-6h, and a polymerization product is obtained;
[0037] (4) dispersing, washing and drying the polymer product of step (3) to obtain a final product;
[0038] Specifically, dispersion: after the reaction is completed, a dispersant is added to the polymer product of step (3), and the dispersant disperses the polymer product into a solid powder with particles less than 1 mm. The mass ratio of the polymer product of step (3) to the dispersant is 1:4-10, preferably 1:6;
[0039] Washing: Wash the dispersed solid powder with an acidic aqueous solution and pure water at 60-100°C, respectively, until the metal ion content drops below 100 ppm;
[0040] Drying: Dry the washed solid powder at 120-160°C for 8-24h.
[0041] In the step (1) of the present invention, the molar ratio of 1,3-dihydrobenzimidazol-2-one, 2,6-difluorobenzonitrile and 4,4'-difluorobenzophenone is preferably 4:3:1, the catalyst is selected from any one of anhydrous sodium carbonate and anhydrous potassium carbonate, the organic solvent is selected from any one of diphenyl sulfone, diisopropylbenzene peroxide, N,N-dimethylformamide, cyclopentane, N-cyclohexylpyrrolidone or a combination of several thereof, and the organic solvent is preferably dehydrated. The dehydration process of each organic solvent is a conventional technical means in the art and will not be described in detail herein.
[0042] The dehydration of the reaction system in step (1) of the present invention can be carried out by adding a water-carrying agent together with the reaction raw materials to the reaction system before the reaction begins, and the water-carrying agent and water are azeotropically dehydrated. Specifically, during the reaction of 1,3-dihydrobenzimidazol-2-one with the catalyst, the water-carrying agent and water azeotropically remove water in the reaction system. After the catalytic reaction is completed, the temperature is maintained at 140-200°C for 1-2 hours, and the water-carrying agent continues to remove water from the reaction system, so that the water content of the reaction system is less than or equal to 1000ppm. The water-carrying agent in step (1) is selected from xylene or toluene, and the volume ratio of the water-carrying agent to the organic solvent is 0.4-0.6:1.
[0043] The dehydration of the reaction system in step (1) of the present invention can also be carried out by subjecting the reaction system to vacuum distillation dehydration at 140-200° C. for 1-2 hours after the catalytic reaction is completed.
[0044] Under the prepolymerization reaction conditions of step (2), the residual water-carrying agent and residual water in the reaction system are removed. The prepolymerization reaction is preferably carried out at 220° C. for 3 hours.
[0045] The polymerization reaction process of step (3) preferably also includes three-stage temperature increase reactions, the reaction temperature of the three-stage temperature increase reactions is 240-320°C, and the reaction time is 2-8h. In the present invention, it is preferred to carry out a first-stage temperature increase reaction at 180°C, and after reacting for 2h, heat up to 190°C for a second-stage temperature increase reaction, the reaction time is 2h, and then heat up to 240°C for a third-stage temperature increase reaction, react for 8h to obtain the final product, and the heating rate is preferably 1°C / min.
[0046] In the present invention, the dispersant in step (4) is selected from any one of water, methanol and ethanol, the acidic solution is a phosphoric acid aqueous solution with a mass fraction of 3%-50%, and steps (1)-(3) are all carried out under an inert gas, and the inert gas is selected from any one of argon, nitrogen, helium or a combination of several gases.
[0047] The present invention also provides a novel self-flame retardant thermoplastic polyaryl ketone resin synthesized by the above preparation method. The structure of the thermoplastic polyaryl ketone resin is shown below:
[0048] ;
[0049] Wherein, m and n are the numbers of two repeating units, and both m and n are positive integers, 5≤m≤500, 5≤n≤500.
[0050] In the presence of a catalyst, the synthesis process of thermoplastic polyaryl ketone resin is:
[0051] .
[0052] Specifically, in the salt-forming reaction of step (1), the reaction temperature is set at 140-200°C because when the reaction temperature is lower than 140°C, the reaction between 1,3-dihydrobenzimidazol-2-one and the catalyst is too slow, and when the temperature is higher than 200°C, the reaction monomer is easily oxidized. The reaction product water is taken away by a water-carrying agent or vacuum distillation to promote the catalytic reaction to proceed to the right.
[0053] In the present invention, the prepolymerization reaction mainly occurs in step (2). During the reaction of 1,3-dihydrobenzimidazol-2-one with the catalyst in step (1), a small amount of monomers will undergo prepolymerization reaction.
[0054] In the polymerization reaction of step (3) of the present invention, a first-stage temperature increase reaction is used to avoid the violent polymerization or bubble generation caused by excessive temperature in the early stage of polymerization, and a second-stage temperature increase reaction and a third-stage temperature increase reaction are used to increase the reaction temperature, thereby ensuring that the reaction monomers are more completely polymerized and improving the quality of the product. During the polymerization reaction, the reaction endpoint can be determined based on the viscosity of the material. In step (4), the solid powder is washed with an acidic aqueous solution to reduce the metal ion content in the solid powder and improve the purity of the solid powder. Specific embodiments Example 1
[0055] Raw material ratio: weigh 6.85 g (51.12 mmol) of 1,3-dihydrobenzimidazol-2-one, 3.59 g (25.79 mmol) of 2,6-difluorobenzonitrile, 5.63 g (25.79 mmol) of 4,4'-difluorobenzophenone, 6.07 g of anhydrous sodium carbonate, and 50 mL of organic solvent N,N-dimethylformamide (purity 99.9%);
[0056] Experimental steps:
[0057] (1) Under slow stirring and nitrogen conditions, add 1,3-dihydrobenzimidazol-2-one, 4,4'-difluorobenzophenone, 2,6-difluorobenzonitrile, anhydrous sodium carbonate and N,N-dimethylformamide to a 250mL four-necked round-bottom flask according to the raw material ratio, heat the reaction system to 140°C, and react 1,3-dihydrobenzimidazol-2-one with anhydrous sodium carbonate for 1.5 hours to generate disodium salt. The reaction mixture is a white slurry. Maintain the temperature at 140°C and perform vacuum distillation on the reaction system for 1.5 hours to remove water from the reaction system, producing a viscous brown slurry;
[0058] (2) Prepolymerization: The reaction system was heated to 160°C for prepolymerization for 4 hours. The residual water was distilled into the water separator and the reaction mixture was a viscous brown slurry.
[0059] (3) Polymerization reaction: The reaction temperature was raised to 180°C at a heating rate of 1°C / min, and the reaction was carried out for 2 h. The temperature was then raised to 190°C and the reaction was carried out for 2 h. Finally, the temperature was raised to 240°C and the polymerization reaction was carried out for 8 h to obtain a polymer product.
[0060] (4) Dispersion: According to the mass ratio of the polymer product to methanol in step (3) being 1:6, the polymer product and methanol are added into a pulverizer, the polymer product is pulverized, and the polymer product is crushed into solid powders less than 0.5 mm and then filtered;
[0061] Washing: at 80°C, add the filtered solid powder and 60 mL of 50% H3PO4 into a four-necked flask, with the stirrer speed at 350 rpm, stir for 5 min and filter, then mix and stir with 350 mL of pure water for 1 h, then filter, repeat the washing process of adding H3PO4 and pure water twice, measure the ionic conductivity of the filtrate, and the sodium ion content is less than 100 ppm;
[0062] Drying: The washed solid powder was dried at 140°C for 12 h to obtain the final product.
[0063] A novel self-flame retardant thermoplastic polyaryl ketone resin was obtained by using the experimental steps of this embodiment. Figure 1 : is the DSC curve of the thermoplastic polyaryl ketone resin prepared in this embodiment. The glass transition temperature of the thermoplastic polyaryl ketone resin is 289.27°C. Example 2
[0064] Raw material ratio: 1,3-dihydrobenzimidazol-2-one 6.85g (51.12mmol), 2,6-difluorobenzonitrile 3.59g (25.78mmol), 4,4'-difluorobenzophenone 5.63g (25.79mmol), anhydrous sodium carbonate 5.85g, organic solvent diphenyl sulfone (purity 99.9%) 50mL, dehydrating agent xylene (purity 99.9%) 20mL;
[0065] Experimental steps:
[0066] (1) Under slow stirring and argon conditions, add 1,3-dihydrobenzimidazol-2-one, 4,4'-difluorobenzophenone, 2,6-difluorobenzonitrile, anhydrous sodium carbonate, diphenyl sulfone and xylene to a 250mL four-necked round-bottom flask according to the raw material ratio, heat the reaction system to 140°C, and 1,3-dihydrobenzimidazol-2-one reacts with anhydrous sodium carbonate for 2 hours to generate disodium salt. The reaction system is a white slurry. Raise the temperature to 160°C, and azeotropize xylene and water for 2 hours to produce a viscous yellow slurry. The water in the reaction system enters the water separator with the xylene. The xylene in the upper layer of the water separator refluxes into the four-necked round-bottom flask, and the water in the lower layer of the water separator is directly released. The water content of the reaction system is less than 5ppm;
[0067] (2) Prepolymerization reaction: The reaction system temperature is heated to 200°C, and the salt in step (1) is subjected to prepolymerization reaction with 4,4'-difluorobenzophenone and 2,6-difluorobenzonitrile respectively. The reaction time is 2 hours, and the residual xylene and water in the reaction system are distilled into the water separator. The reaction system is a viscous yellow slurry;
[0068] (3) The reaction temperature was first raised to 260°C at a heating rate of 5°C / min, and the reaction was continued for 2 h, and then the temperature was raised to 280°C and the reaction was continued for 6 h to obtain a polymerization product;
[0069] (4) Dispersion: According to the mass ratio of the polymer product to water in step (3) being 1:4, the polymer product and water are added into a pulverizer, the polymer product is pulverized, and the polymer product is crushed into solid powder less than 0.5 mm and then filtered;
[0070] Washing: Control the temperature at 60°C, add the filtered solid powder and 300mL of 10% H3PO4 into a four-necked flask, set the stirrer speed at 250rmp, stir for 3min and filter, then mix with 300mL of pure water and stir for 1h and filter again, repeat the process of adding pure water for washing three times, measure the ionic conductivity of the filtrate, and the sodium ion content is less than 100ppm;
[0071] Drying: The washed solid powder was dried at 120°C for 24 h to obtain the final product.
[0072] A new type of self-flame retardant thermoplastic polyaryl ketone resin was obtained by using the experimental steps of this embodiment. Example 3
[0073] Raw material ratio: weigh 6.85 g (51.12 mmol) of 1,3-dihydrobenzimidazol-2-one, 5.391 g (38.68 mmol) of 2,6-difluorobenzonitrile, 2.81 g (12.89 mmol) of 4,4'-difluorobenzophenone, 7.77 g of anhydrous potassium carbonate, 50 mL of organic solvent sulfolane (purity 99.9%), and 25 mL of dehydrating agent toluene (purity 99.9%);
[0074] Experimental steps:
[0075] (1) Under slow stirring and nitrogen conditions, add 1,3-dihydrobenzimidazol-2-one, 4,4'-difluorobenzophenone, 2,6-difluorobenzonitrile, anhydrous potassium carbonate, cyclopentane sulfone and toluene to a 250 mL four-necked round-bottom flask according to the raw material ratio, heat the reaction system to 160°C, and 1,3-dihydrobenzimidazol-2-one reacts with anhydrous potassium carbonate for 1.5 hours to generate a dipotassium salt. The reaction mixture is a white slurry. The temperature is raised to 180°C, and toluene continues to azeotropize with water for 1.5 hours to produce a viscous brown slurry. The water in the reaction system enters the water separator with the toluene. The toluene in the upper layer of the water separator refluxes into the four-necked round-bottom flask, and the water in the lower layer of the water separator is directly discharged. The water content of the reaction system is less than 100 ppm.
[0076] (2) Prepolymerization: The reaction system was heated to 220°C for prepolymerization for 3 hours. The remaining toluene and water were distilled into the water separator. The reaction mixture was a viscous brown slurry.
[0077] (3) Polymerization reaction: The reaction temperature was raised to 270°C at a heating rate of 1°C / min and the reaction was carried out for 2.5 h to obtain a medium-viscosity brown paste. The temperature was then raised to 290°C and the reaction was carried out for 5 h to obtain a polymerization product.
[0078] (4) Dispersion: According to the mass ratio of the polymer product to methanol in step (3) being 1:6, the polymer product and methanol are added into a pulverizer, the polymer product is pulverized, and the polymer product is crushed into solid powders less than 0.5 mm and then filtered;
[0079] Washing: at 80°C, add the filtered solid powder and 60 mL of 50% H3PO4 into a four-necked flask, with the stirrer speed at 350 rpm, stir for 5 min and filter, then mix and stir with 350 mL of pure water for 1 h, then filter, repeat the washing process of adding H3PO4 and pure water three times, measure the ionic conductivity of the filtrate, and the potassium ion content is less than 100 ppm;
[0080] Drying: The washed solid powder was dried at 140°C for 12 h to obtain the final product.
[0081] A new type of self-flame retardant thermoplastic polyaryl ketone resin was obtained by using the experimental steps of this embodiment. Example 4
[0082] Raw material ratio: weigh 6.85 g (51.12 mmol) of 1,3-dihydrobenzimidazol-2-one, 1.83 g (13.15 mmol) of 2,6-difluorobenzonitrile, 8.61 g (39.45 mmol) of 4,4'-difluorobenzophenone, 7.91 g of anhydrous potassium carbonate, 56 mL of organic solvent N-cyclohexylpyrrolidone (purity 99.9%), and 30 mL of dehydrating agent xylene (purity 99.9%);
[0083] Experimental steps:
[0084] (1) Under slow stirring and helium conditions, add 1,3-dihydrobenzimidazol-2-one, 4,4'-difluorobenzophenone, 2,6-difluorobenzonitrile, anhydrous potassium carbonate, N-cyclohexylpyrrolidone and xylene to a 250mL four-necked round-bottom flask according to the raw material ratio, heat the reaction system to 200°C, and react 1,3-dihydrobenzimidazol-2-one with anhydrous potassium carbonate for 1 hour to generate a dipotassium salt to obtain a white slurry. Keep the temperature at 200°C, and continue to azeotropically dehydrate xylene and water for 1 hour to produce a viscous yellow slurry. The water in the reaction system enters the water separator with the xylene. The xylene in the upper layer of the water separator refluxes into the four-necked round-bottom flask, and the water in the lower layer of the water separator is directly released. The water content of the reaction system is less than 1000ppm;
[0085] (2) Prepolymerization: The reaction system temperature was maintained at 260°C for prepolymerization for 6 hours. The remaining xylene and water were distilled into the water separator. The reaction mixture was a viscous yellow slurry.
[0086] (3) Polymerization reaction: The reaction temperature was raised to 280°C at a heating rate of 3°C / min, and the reaction was carried out at 280°C for 3 h. The temperature was then raised to 320°C under pressure and the reaction was carried out for 2 h to obtain a polymerization product.
[0087] (4) Dispersion: Add the polymer product and ethanol into a pulverizer at a mass ratio of 1:10 according to the polymer product of step (3), pulverize the polymer product, break the polymer product into solid powders less than 1 mm, and then filter;
[0088] Washing: at 100°C, add the filtered solid powder and 350 mL of 3% H3PO4 into a four-necked flask, with the stirrer speed at 350 rpm, stir for 10 min and filter, then mix and stir with 350 mL of pure water for 1.5 h, then filter, repeat the washing process of adding H3PO4 and pure water four times, measure the ionic conductivity of the filtrate, and the potassium ion content is less than 100 ppm;
[0089] Drying: Dry the washed solid powder at 160°C for 8 h.
[0090] A new type of self-flame retardant thermoplastic polyaryl ketone resin was obtained by using the experimental steps of this embodiment.
[0091] Effect test of the thermoplastic polyaryl ketone resin of the present invention
[0092] The thermoplastic polyaryl ketone resin obtained in Examples 1-4 was subjected to multiple differential scanning calorimetry (DSC), inherent viscosity and metal ion content tests to obtain the data in Table 1. The DSC test conditions are: 50-430°C, heating at a rate of 20°C / min; the inherent viscosity was tested by a conventional method for measuring kinematic viscosity; metal ion content test: 350 mL of pure water was added to the thermoplastic polyaryl ketone resin product, stirred for 5 minutes and then filtered, the ionic conductivity in the filtrate was measured, and the metal ion content was obtained according to the ionic conductivity calculation formula.
[0093] Table 1 Thermoplastic polyaryl ketone resin performance test table
[0094]
[0095] It can be concluded from Table 1 that the thermoplastic polyaryl ketone resin prepared by the synthesis method of the present invention has a higher glass transition temperature, which is 253°C and above, which is higher than the glass transition temperature of ordinary polyaryl sulfone. The polymerization molecular weight and Tg of the polyaryl ketone resin are closely related to the raw material ratio. It can be seen from Table 1 that under the same conditions, the higher the molar proportion of 2,6-difluorobenzonitrile in the polymerization monomer, the higher the Tg of the prepared thermoplastic polyaryl ketone resin. When the molar ratio of 2,6-difluorobenzonitrile: 4,4'-difluorobenzophenone is ≥1, the Tg of the thermoplastic polyaryl ketone resin is ≥305°C. When the molar ratio of 1,3-dihydrobenzimidazol-2-one: 2,6-difluorobenzonitrile: 4,4'-difluorobenzophenone is 4:3:1, the Tg of the thermoplastic polyaryl ketone resin reaches 327°C. It shows that the thermoplastic polyaryl ketone resin prepared by the present invention has higher heat resistance. The DSC test on the thermoplastic polyaryl ketone resin was repeated, and the glass transition temperature remained basically unchanged, indicating that the thermoplastic polyaryl ketone resin has good heat resistance and stability. The residual metal ions in the thermoplastic polyaryl ketone resin are less than or equal to 98 ppm, indicating that the metal ions are effectively removed by washing, the purity of the thermoplastic polyaryl ketone resin is improved, and the application scenarios are broader.
[0096] The thermoplastic polyaryl ketone resins obtained in Examples 1-4 were tested for nitrogen content (referring to the mass fraction of nitrogen in the polymer), flame retardancy and oxygen index, respectively, and Table 2 was obtained, wherein the nitrogen content was tested by elemental analysis, the flame retardancy was tested according to the UL-94 fire rating test standard, and the oxygen index test standard was GB 50222-2017 "Code for Fire Protection Design of Interior Decoration of Buildings".
[0097] Table 2 Thermoplastic polyaryl ketone resin performance test table
[0098]
[0099] As can be seen from Table 2, the nitrogen content of the thermoplastic polyaryl ketone resin prepared by the present invention is ≥9.2%, which is higher than the nitrogen content of conventional polyaryl ether ketone and polyaryl sulfone materials, and the UL-94 fire rating is the highest level V0, and the oxygen index is ≥33.1%, indicating that the thermoplastic polyaryl ketone resin has high flame retardancy. The trend of nitrogen content change in Table 2 is consistent with the trend of glass transition temperature change in Table 1, because the higher the molar proportion of 2,6-difluorobenzonitrile in the reaction monomer, the higher the nitrogen content in the obtained thermoplastic polyaryl ketone resin, which makes the flame retardancy of the thermoplastic polyaryl ketone resin better and the glass transition temperature higher.
[0100] In the present invention, 1,3-dihydrobenzimidazol-2-one contains nitrogen-hydrogen reaction sites, and can undergo a coupling reaction similar to carbon-carbon bonding with 2,6-difluorobenzonitrile and 4,4'-difluorobenzophenone under the catalysis of a catalyst to obtain a thermoplastic polyaryl ketone resin. Therefore, the present invention uses 1,3-dihydrobenzimidazol-2-one as the main monomer, directly polymerizes with 4,4'-difluorobenzophenone and 2,6-difluorobenzonitrile, introduces nitrogen into the polyaryl ketone material, increases the content of nitrogen in the polyaryl ketone material, and utilizes the good flame retardant properties of nitrogen to improve the flame retardancy of the polyaryl ketone resin, which can be used as a flame retardant material. The bond energy of the carbon-nitrogen bond enables the thermoplastic polyaryl ketone resin obtained by the present invention to have a high glass transition temperature, the glass transition temperature is greater than or equal to 253°C, can be applied to high temperature environments, and has a long service life.
[0101] It should be understood that the purpose of these embodiments is only to illustrate the present invention and is not intended to limit the protection scope of the present invention. In addition, it should also be understood that after reading the technical content of the present invention, those skilled in the art can make various changes, modifications and / or variations to the present invention, and all of these equivalent forms also fall within the protection scope defined by the claims attached to this application.
Claims
1. A method for synthesizing a self-flame retardant thermoplastic polyaryl ketone resin, characterized in that: The following steps are involved: (1) Under an inert atmosphere, 1,3-dihydrobenzimidazol-2-one, 4,4'-difluorobenzophenone, 2,6-difluorobenzonitrile, a catalyst and an organic solvent are added to a reaction vessel and stirred, and the temperature is raised to 140-200° C. for reaction for 1-2 hours, 1,3-dihydrobenzimidazol-2-one reacts with the catalyst to generate salt and water, and the reaction system is dehydrated so that the water content of the reaction system is less than or equal to 1000 ppm; (2) Prepolymerization reaction: reacting at 160-260° C. for 2-6 hours, wherein the salt in step (1) reacts with 4,4'-difluorobenzophenone and 2,6-difluorobenzonitrile to obtain a prepolymer product; (3) Polymerization reaction: heat to 180-320°C, react for 2-8 hours to obtain a polymer product; (4) dispersing, washing and drying the polymer product of step (3) to obtain a final product; The molar ratio of 1,3-dihydrobenzimidazol-2-one, 2,6-difluorobenzonitrile and 4,4'-difluorobenzophenone is 4:1-3:1-3; The molar ratio of the 1,3-dihydrobenzimidazol-2-one, the catalyst and the organic solvent is 1:1.08-1.12:5-15.
2. The method for synthesizing a self-flame retardant thermoplastic polyaryl ketone resin according to claim 1, characterized in that: In step (1), the molar ratio of 1,3-dihydrobenzimidazol-2-one, 2,6-difluorobenzonitrile and 4,4'-difluorobenzophenone is 4:3:
1.
3. The method for synthesizing a self-flame retardant thermoplastic polyaryl ketone resin according to claim 1, characterized in that: In step (1), the reaction temperature of 1,3-dihydrobenzimidazol-2-one and the catalyst is 160-180°C.
4. The method for synthesizing a self-flame retardant thermoplastic polyaryl ketone resin according to claim 1, characterized in that: In step (1), the catalyst is selected from anhydrous sodium carbonate or anhydrous potassium carbonate, and the organic solvent is selected from any one of diphenyl sulfone, diisopropylbenzene peroxide, N,N-dimethylformamide, cyclopentane, and N-cyclohexylpyrrolidone, or a combination of several thereof.
5. The method for synthesizing a self-flame retardant thermoplastic polyaryl ketone resin according to claim 1, characterized in that: The prepolymerization reaction in step (2) is carried out at 220° C. for 3 h to obtain a prepolymerization product.
6. The method for synthesizing a self-flame retardant thermoplastic polyaryl ketone resin according to claim 1, characterized in that: Step (3) includes a first temperature rising reaction and a second temperature rising reaction, wherein both the first temperature rising reaction and the second temperature rising reaction adopt gradient heating, and the heating rate is 1-5°C / min.
7. The method for synthesizing a self-flame retardant thermoplastic polyaryl ketone resin according to claim 6, characterized in that: The reaction temperature of the first stage temperature-raising reaction is 180-280° C., and the reaction time of the first stage temperature-raising reaction is 2-3 hours.
8. The method for synthesizing a self-flame retardant thermoplastic polyaryl ketone resin according to claim 6, characterized in that: The reaction temperature of the second-stage temperature-raising reaction is 190-320° C., and the reaction time of the second-stage temperature-raising reaction is 2-6 hours.
9. The method for synthesizing a self-flame retardant thermoplastic polyaryl ketone resin according to claim 1, characterized in that: The washing process of step (4) is: washing the solid powder with an acidic aqueous solution and pure water for multiple times at 60-100° C. until the metal ion content drops below 100 ppm; The acidic aqueous solution is a phosphoric acid aqueous solution with a mass fraction of 3%-50%.
10. A self-flame retardant thermoplastic polyaryl ketone resin obtained by the synthesis method according to any one of claims 1 to 9, characterized in that: The thermoplastic polyaryl ketone resin has the following general structural formula: ; Wherein, m and n are the numbers of two repeating units, and both m and n are positive integers, 5≤m≤500, 5≤n≤500.
Citation Information
Patent Citations
Polyaryletherketone and method for preparing same
CN103450478A
Polymer electrolyte composition, and polymer electrolyte membrane, membrane-electrode assembly, and polymer electrolyte fuel cell each using same
CN103998527A